2020
DOI: 10.3332/ecancer.2020.1092
|View full text |Cite
|
Sign up to set email alerts
|

Excellent response to erlotinib in breast carcinoma with rare EGFR mutation—a case report

Abstract: Triple negative breast carcinoma is a problematic subtype with poor outcomes. Many clinical trials are underway to find possible target to increase treatment options. Epidermal growth factor receptor (EGFR) has emerged as one such molecule which is over expressed in some of these patients and can be targeted by tyrosine kinase inhibitors. We describe a diagnostically challenging case of metastatic breast carcinoma, with extensive lung disease and poor Eastern Cooperative Oncology Group (ECOG) performance statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a preclinical study, osimertinib also showed marked efficacy in EGFR -mutated glioblastoma [ 81 ]. For a metastatic breast cancer patient with EGFR L861Q mutation in a resort situation, treatment with anti-EGFR provided 6 months of disease control [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical study, osimertinib also showed marked efficacy in EGFR -mutated glioblastoma [ 81 ]. For a metastatic breast cancer patient with EGFR L861Q mutation in a resort situation, treatment with anti-EGFR provided 6 months of disease control [ 82 ].…”
Section: Discussionmentioning
confidence: 99%